A Multi-level Approach to Vietnam Foreign Policy: From Security Preoccupation to Middle Power Role. Issue 4 (4th July 2021) - Tinh, Le Dinh
Abstract: Prior to 1995 when Vietnam joined ASEAN and normalized relationship with the United States, the overriding concern was security as could be well explained by realism. Vietnam has made several critical, strategic moves since 1995 and by 2030 the country may be able to act internationally as an emerging middle power. Taking a multi-level approach and empirical evidences of 35 years of Doi Moi (renovation), this article attempts to clarify as to how Vietnam has been in a better position to ensure the security goal by embarking on an ambitious development strategy and expanding its international role.